SPECIFIC ASPECTS OF ORGANIZING ACCOUNTING WORK IN BUDGETARY ORGANIZATIONS OF REPUBLIC - Khusаnov Asadbek Akbar o‘g‘li (THE INNOVATION ECONOMY, 2026)
This article talks about the features of accounting in budgetary organizations and accounting in social institutions. An analysis of the funds allocated for the social sphere from the state budget is presented. The improvement of the organizational, technical and methodological aspects of accounting in budgetary organizations is scientifically substantiated.